Clinical and cost implications of amyloid beta detection with amyloid beta positron emission tomography imaging in early Alzheimer's disease – the case of florbetapir. (3rd April 2017) - Hornberger, John; Bae, Jay; Watson, Ian; Johnston, Joe; Happich, Michael
Abstract: Objective: Amyloid beta (Aβ) positron emission tomography (PET) imaging helps estimate Aβ neuritic plaque density in patients with cognitive impairment who are under evaluation for Alzheimer's disease (AD). This study aims to evaluate the cost-effectiveness of the Aβ-PET scan as an adjunct to standard diagnostic assessment for diagnosis of AD in France, using florbetapir as an example. Methods: A state-transition probability analysis was developed adopting the French Health Technology Assessment (HTA) perspective per guidance. Parameters included test characteristics, rate of cognitive decline, treatment effect, costs, and quality of life. Additional scenarios assessed the validity of the analytical framework, including: (1) earlier evaluation/treatment; (2) cerebrospinal fluid (CSF) as a comparator; and (3) use of other diagnostic procedures. Outputs included differences in quality-adjusted life years (QALYs), costs, and incremental cost-effectiveness ratios (ICERs). All benefits and costs were discounted for time preferences. Sensitivity analyses were performed to assess the robustness of findings and key influencers of outcomes. Results: Aβ-PET used as an adjunct to standard diagnostic assessment increased QALYs by 0.021 years and 10 year costs by €470 per patient. The ICER was €21, 888 per QALY gained compared to standard diagnostic assessment alone. When compared with CSF, Aβ-PET costs €24, 084 per QALY gained. In other scenarios, Aβ-PET was consistently cost-effective relative to the commonly used affordability threshold (€40, 000 per QALY). Over 95% of simulations in the sensitivity analysis were cost-effective. Conclusion: Aβ-PET is projected to affordably increase QALYs from the French HTA perspective per guidance over a range of clinical scenarios, comparators, and input parameters.